DIALYSIS DECISION-MAKING WITH ELDERLY PATIENTS: A QUALITATIVE STUDY OF NEPHROLOGISTS. (11th November 2018) - Ladin, K; Pandya, R; Weiner, D; Meyer, K; Perrone, R; Wong, J
Abstract: For older adults with advanced kidney disease, dialysis may not confer survival benefit over conservative management (CM), but is associated with significant reduction in quality of life. Yet, dialysis incidence among older adults has increased more than in any other age group; and many regret dialysis. Despite guidelines recommending shared decision-making and discussion of CM, nephrologists vary significantly in their approaches. We examined how nephrologists' ethical perspectives shape their approach towards decision-making with patients, and characterized different models of decision-making. In this qualitative study, we interviewed a national sample of purposively sampled nephrologists (n=35) from 18 practices. Interviews continued until thematic saturation. Data were analyzed using typological and thematic approaches. Four distinct approaches to decision-making emerged: paternalist, informative (patient-led), interpretative (navigator), and institutionalist. Only one-third of providers presented CM to patients; all of whom followed either informative or interpretative approaches. Five themes characterized differences between these approaches, including: patient autonomy, engagement and deliberation (disclosing all options, presenting options neutrally, eliciting patient values, explicit treatment recommendation), influence of institutional norms, importance of clinical outcomes, and physician role. Paternalists and institutionalists viewed initiation of active treatment as a measure of success, interpretative and informative nephrologists focused on patient engagement, quality of life, and aligning patient values with treatment. The interpretive model best achieved shared decision-making. Our findings clarify how differences in perceptions of physician role, patient autonomy, and successful versus unsuccessful encounters contribute to variation in care. These distinct approaches highlight a need for greater tailoring in interventions and shared decision-making guidelines.